MEKANISME PEMBUBARAN PERSEKUTUAN KOMANDITER (COMMANDITAIRE VENNOOTSCHAP) - , JESHIMOB D.C GIAWA, Rr. Dinarjati Eka P. S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The author takes the title Kommanditai regesellschaft Dissolution Mechanism because the author wishes to learn more about how Kommanditaire Gesellschaftoroften called by CV indisbanded, previously the author very little knowledge about this Kommanditaire Gesellschaft that makes the writer moved to take the title of this thesis related with Kommanditaire Gesellschaft. After learning more about this Kommanditaire Gesellschaft, the authors obtain a new knowledge that the writer will be very useful as a preparation for entering the word of work. Run approximately two (2) months of the authors carry outfield work practice in the office of Notary and PPAT Muhammad Agus Hanafi, SH. Many benefits, especially writers get experience that can not be obtained simply by reading and studying the book, because in the world of work is needed not only knowledge but also the attitude of a person's professionalism.